Renin, a marker for left ventricular hypertrophy, in primary aldosteronism: a cohort study. Issue 5 (8th October 2021) - Köhler, Anton; Sarkis, Anna-Lina; Heinrich, Daniel Alexander; Müller, Lisa; Handgriff, Laura; Deniz, Sinan; Schneider, Holger; Künzel, Heike; Ladurner, Roland; Reincke, Martin; Adolf, Christian
Abstract : Context: Primary aldosteronism (PA) causes left ventricular hypertrophy (LVH) via hemodynamic factors and directly by aldosterone effects. Specific treatment by mineralocorticoid receptor antagonists (MRA) or adrenalectomy (ADX) has been reported to improve LVH. However, the cardiovascular benefit could depend on plasma renin concentration (PRC) in patients on MRA. Patients and objective: We analyzed data from 184 patients from the Munich center of the German Conn's Registry, who underwent echocardiography at the time of diagnosis and 1 year after treatment. To assess the effect of PRC on cardiac recovery, we stratified patients on MRA according to suppression ( n = 46) or non-suppression of PRC ( n = 59) at follow-up and compared them to PA patients after ADX ( n = 79). Results: At baseline, patients treated by ADX or MRA had comparable left ventricular mass index (LVMI, 61.7 vs 58.9 g/m 2.7, P = 0.591). Likewise, patients on MRA had similar LVMI at baseline, when stratified into treatment groups with suppressed and unsuppressed PRC during follow-up (60.0 vs 58.1 g/m 2.7, P = 0.576). In all three groups, we observed a significant reduction in LVMI following treatment ( P < 0.001). However, patients with suppressed PRC had no decrease in pro-BNP levels, and the reduction of LVMI was less intense than in patients with unsuppressed PRC (4.1 vs 8.2 g/m 2.7, P = 0.033) or after ADX (9.3 g/m 2.7, P = 0.019). Similarly, in multivariate analysis, higher PRC was correlated with the regression of LVH. Conclusion: PA patients with suppressed PRC on MRA show impaired regression of LVH. Therefore, dosing of MRA according to PRC could improve their cardiovascular benefit.